Formation of a Surficial Bifunctional Nanolayer on Nb2O5 for Ultrastable Electrodes for Lithium‐Ion Battery. Issue 19 (21st March 2017) - Cheong, Jun Young; Kim, Chanhoon; Jung, Ji‐Won; Yoon, Ki Ro; Cho, Su‐Ho; Youn, Doo‐Young; Jang, Hye‐Yeon; Kim, Il‐Doo
Abstract : Safe and long cycle life electrode materials for lithium‐ion batteries are significantly important to meet the increasing demands of rechargeable batteries. Niobium pentoxide (Nb2 O5 ) is one of the highly promising candidates for stable electrodes due to its safety and minimal volume expansion. Nevertheless, pulverization and low conductivity of Nb2 O5 have remained as inherent challenges for its practical use as viable electrodes. A highly facile method is proposed to improve the overall cycle retention of Nb2 O5 microparticles by ammonia (NH3 ) gas‐driven nitridation. After nitridation, an ultrathin surficial layer (2 nm) is formed on the Nb2 O5, acting as a bifunctional nanolayer that allows facile lithium (Li)‐ion transport (10–100 times higher Li diffusivity compared with pristine Nb2 O5 microparticles) and further prevents the pulverization of Nb2 O5 . With the subsequent decoration of silver (Ag) nanoparticles (NPs), the low electric conductivity of nitridated Nb2 O5 is also significantly improved. Cycle retention is greatly improved for nitridated Nb2 O5 (96.7%) compared with Nb2 O5 (64.7%) for 500 cycles. Ag‐decorated, nitridated Nb2 O5 microparticles and nitridated Nb2 O5 microparticles exhibit ultrastable cycling for 3000 cycles at high current density (3000 mA g −1 ), which highlights the importance of the surficial nanolayer in improving overall electrochemical performances, in addition to conductive NPs. Abstract : A surficial bifunctional nanolayer is adopted on Nb2 O5 microparticles by a simple nitridation process, where it results in higher ionic transport and further prevents the pulverizaton of Nb2 O5 . Upon decoration of Ag nanoparticles, electric conductivity of Nb2 O5 is further improved, resulting in ultralong cycle retention at high current density (3000 mA g −1 ).